Study of damage profiles and energy calculation of arsenic ions during ion implantation on Germanium - Giri, K; Kandel, B (BIBECHANA, 2020)
Computational calculation of energy loss and damage profiles when implanted by arsenic ions on amorphous germanium during ion implantation had been carried out. The required energies for doping of arsenic ion on germanium, in order to obtain maximum damage at 600 Å, were calculated using SRIM. These ions when implanted on germanium causes the production of germanium recoils, vacancy-interstitial pairs, and phonons during the collision process. For 140 keV arsenic ion, the energy consumption for ionization, phonon production and vacancies creation are 39.634 keV (28.31% of incident energy), 90.888 keV (64.92% of incident energy) and 9.478 keV (6.77% of incident energy), respectively. The amount of target displacement, replacement collisions and vacancies were also evaluated. Doping of arsenic ions on germanium also revealed that the energy loss due to nuclear stopping was greater than electronic stopping. Significantly, surface hardness and electrical conductivity on germanium cannot be improved with calculated energies. BIBECHANA 17 (2020) 96-103